1982
DOI: 10.1002/jsfa.2740330512
|View full text |Cite
|
Sign up to set email alerts
|

A study of polyphenols in the seeds and leaves of guar (Cyamopsis tetragonoloba L. Taub)

Abstract: Gallotannins, gallic acid, gallic acid derivatives, myricetin-7-glucoside-3-glycoside, kaempferol-7-glucoside-3-glycoside, kaempferol-3-rutinoside, kaempferoI-3-glucoside, chlorogenic acid, caffeic acid and ellagic acid were derived from guar seeds and identified by chromatographic and spectral analysis. Myricetin-7-glucoside-3-glycoside, kaempferol-7-glucoside-3-glycoside, kaempferol-3-rut inoside, kaempferol-3-glucoside, quercetin-3-rutinoside, 2,3,4-trihydroxybenzoic acid, texasin-7-O-glucoside, daidzein-7-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…The fragment ion peak of the aglycone at m/z 285 is in accordance with the molecular formula C 16 H 13 O 5 of dihydroxy and one methoxy substitution pattern. The mass spectral data are in agreement with those reported for texasin 7-O-hexoside (Kaushal & Bhatia, 1982). Hence, the fragmentation pathway underwent the Retro-Diels Alder reaction giving rise to ring-A fragment at m/z 153 and m/z 132, and there were further fragments giving rise to m/z 124.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The fragment ion peak of the aglycone at m/z 285 is in accordance with the molecular formula C 16 H 13 O 5 of dihydroxy and one methoxy substitution pattern. The mass spectral data are in agreement with those reported for texasin 7-O-hexoside (Kaushal & Bhatia, 1982). Hence, the fragmentation pathway underwent the Retro-Diels Alder reaction giving rise to ring-A fragment at m/z 153 and m/z 132, and there were further fragments giving rise to m/z 124.…”
Section: Resultssupporting
confidence: 88%
“…UV absorption spectrum in MeOH exhibited two characteristic absorption maxima of isoflavone at 326 nm (band-I, cinnamoyl system) and 258 nm (band-II, benzoyl system). Moreover, it gave the same absorbency in accordance with texasin 7-O-glucoside with different diagnostic shift reagents (Kaushal & Bhatia, 1982). The ESI-MS spectra exhibited a quasi molecular ion at m/z 448 and a fragment ion peak at 285 which were ascribed to [M+1] + and [M-162] + suggesting the presence of one glycosyl moiety (hexose).…”
Section: Resultsmentioning
confidence: 63%
“…Approximately 88% of the nitrogen content in guar korma meal is true protein that makes it potentially useful as an ingredient for feed (Lee et al, 2005). Nadeem et al, (2005) reported that amino acids availability ranged from 64 to 93% for residual guar korma meal, a highly viscous galactomannan polysaccharide, is probably the primary factor responsible for the reported ill effects (Verma and Mc-Nab 1982), although other antinutritional factors such as saponins (Curl et al, 1986) and polyphenols (Kaushal and Bhatia 1982) have been reported to cause liver, kidney, and intestinal damage in mice and rats (Diwan et al, 2000).…”
mentioning
confidence: 99%
“…Viscosity of the guar gum powder varies with the particle size, and moisture. in seed: (i) crude protein -28.3 to 35.0%, (ii) ash content -3.5 to 6.0%, (iii) fat -1.8 to 5.2%, (iv) carbohydrate -38.8 to 59.1%, (v) crude fiber -4.1 to 8.0 and (vi) gum content --23.9 to 34.2% (Pathak et al, 2011 Kaushal and Bhatia (1982) reported the presence of several toxic compounds in cluster bean seeds including gallotannins, gallic acid/its derivatives, myricetin-7-glucoside-3, kaempferol-7-glucoside-3-glycoside, kaempferol-3-rutinoside, kaempferol-3-glucoside, chlorogenic acid, caffeic acid and ellagic acid. Variability in oil content [3.06 to 7.5%] was reported by Joshi et al, (1990 et al, 2000).…”
mentioning
confidence: 99%